NUMERICAL MODELLING OF THE ENDOTHERMIC PROCESS OF THE STEAM REFORMING OF METHANE IN A FIXED BED REFORMER - Dessaune, D. R.; Dias, V. F.; Silva, J. D. (Revista de Engenharia Térmica, 2021)
Thermochemical Packed-Bed (TPB) reformer has been substantially studied in the past years as a promising equipment to investigate the thermochemical conversion of methane (CH4). This work has as main objective a theoretical modelling to describe the process variables of Steam Reforming of Methane (SRM) method in the TPB reformer. The TPB reformer is filled with β-SiC open-cell foam where the thermochemical conversion of CH4 is carried out. The model variables describe the specific aims of work and these objectives can be identified from each equation of the developed mathematical model. This work has been proposed to study two specific aims as (i) the effective thermal conductivity’s effect of the solid phase (λs,eff.) and (ii) molar flows of chemical components. The endothermic reaction temperature’s profiles are notably increased as the numeral value of λs,eff. is raised. The Steam Reforming of Methane (SRM) method is suggested to improve the Production Rate (PR) of H2 regarding the PR of CO. As results, the PR of H2 is of 29.48% while the PR of CO is of 2.76%.